Islamic Republic of Mauritania : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the impact of the global economic slump on the Mauritanian economy, which faces a significant negative terms-of-trade shock that is more persistent than initially envisaged. The impact of the international shock is compounded by a narrow production base, structural weaknesses, and limited policy space related to elevated public debt and pressures on external buffers. The outlook sees a recovery in economic activity to 4.1 percent in 2016, but risks to the outlook are tilted to the downside. The present economic uncertainty has prompted Mauritania to call for an ambitious policy adjustment to diversify the economy and promote inclusive growth for a determined reform agenda.